Systems of Support: The Educators with Disabilities Caucus and Its Mentoring Program - Polly G. Haselden; Pamela K, De Loach; Jennifer Miller; Monica Campbell; Lynn Boyer; Nancy Anderson (Educational Considerations, 2007)
In the field of education, critics have described the experiences of beginning teaching as “sink or swim, trial by fire, or boot camp experiences.”
Keywords: mentoring; programs; educators; Disabilities Caucus; support; policies; procedures; paperwork; accommodations